ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS' MATHEMATICAL COMMUNICATION SKILLS ON SPLDV MATERIAL - Qory Septiani Arsandy; Rahmadani Siregar, Anisa; Rajani Sinaga, Victory; Samuel Gultom, Frans (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Mathematical communication skills remain a persistent challenge for many junior high school students, especially when they are required to represent ideas, explain reasoning, and connect mathematical concepts in the topic of Systems of Linear Equations in Two Variables (SLSV). This study specifically analyzes students' mathematical communication skills in the context of solving SLSV word problems using three main indicators of mathematical communication. This study uses a descriptive qualitative approach with quantitative support involving 20 ninth-grade students from the UPT SMP Negeri 27 Medan selected through purposive sampling. Data were collected through contextual SLSV word problems based on mathematical communication indicators and analyzed using the Miles and Huberman model. The results show that students' mathematical communication skills are generally at a moderate level with an average score of 75.3. In general, students are able to connect various mathematical representations and explain the basic concepts of SLSV, but difficulties remain in maintaining reasoning accuracy, procedural consistency, and correct solution interpretation. This study highlights the need for representation-based learning and problem-based learning to strengthen students' reasoning and communication processes in solving mathematical problems. Kemampuan komunikasi matematika tetap menjadi tantangan yang terus-menerus bagi banyak siswa SMP, terutama ketika mereka dituntut untuk merepresentasikan ide, menjelaskan penalaran, dan menghubungkan konsep matematika dalam topik Sistem Persamaan Linear Dua Variabel (SPLDV). Penelitian ini secara khusus menganalisis kemampuan komunikasi matematis siswa pada konteks penyelesaian soal cerita SPLDV dengan menggunakan tiga indikator utama komunikasi matematis. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan dukungan kuantitatif yang melibatkan 20 siswa kelas sembilan dari UPT SMP Negeri 27 Medan yang dipilih melalui purposive sampling. Data dikumpulkan melalui soal cerita SPLDV kontekstual berdasarkan indikator komunikasi matematika dan dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa keterampilan komunikasi matematika siswa secara umum berada pada tingkat sedang dengan nilai rata-rata 75,3. Secara umum, siswa mampu menghubungkan berbagai representasi matematika dan menjelaskan konsep dasar SPLDV, tetapi kesulitan tetap ada dalam mempertahankan ketepatan penalaran, konsistensi prosedural, dan interpretasi solusi yang tepat. Penelitian ini menyoroti perlunya pembelajaran berbasis representasi dan pembelajaran berbasis masalah untuk memperkuat proses penalaran dan komunikasi siswa dalam memecahkan masalah matematika.